A Median weighted product method for group decision support - Savadogo, Zoïnabo; TAKOUGANG, Stéphane Aimé Metchebon; NIKIEMA, Frédéric; SAWADOGO, Somdouda (International Journal of Applied Mathematical Research, 2021)
When it comes to a multiple criteria and multiple actors decision making problem known as a group decision support problem, the literature generally mentions two ways to aggregate the preferences of decision-makers to achieve consensual outcomes. The first class of group decision support methods run a same multi-criteria method for each decision-maker and thereafter, based on the individual result obtained, find a consensual result. The second class of methods first find a consensus on the preferences of decision-makers and then apply a multi-criteria method based on these consensual preferences to finally have a consensual result. In this work we propose a new method, belonging to the second class of methods for solving group decision problem. This method, called Median Weighted Product Method forGroup Decision Support (MWPM-GDS) aims to achieve quickly and easily results that reflect as accurately as possible the choice of each decision-maker when solving group decision support problems. We applied the proposed method to two well-known examples in the literature and compared the results with those of two other group decision support methods to show its effectiveness.